4(1-3n)-14=4*(2n+3)-9n

Simple and best practice solution for 4(1-3n)-14=4*(2n+3)-9n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(1-3n)-14=4*(2n+3)-9n equation:


Simplifying
4(1 + -3n) + -14 = 4(2n + 3) + -9n
(1 * 4 + -3n * 4) + -14 = 4(2n + 3) + -9n
(4 + -12n) + -14 = 4(2n + 3) + -9n

Reorder the terms:
4 + -14 + -12n = 4(2n + 3) + -9n

Combine like terms: 4 + -14 = -10
-10 + -12n = 4(2n + 3) + -9n

Reorder the terms:
-10 + -12n = 4(3 + 2n) + -9n
-10 + -12n = (3 * 4 + 2n * 4) + -9n
-10 + -12n = (12 + 8n) + -9n

Combine like terms: 8n + -9n = -1n
-10 + -12n = 12 + -1n

Solving
-10 + -12n = 12 + -1n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add 'n' to each side of the equation.
-10 + -12n + n = 12 + -1n + n

Combine like terms: -12n + n = -11n
-10 + -11n = 12 + -1n + n

Combine like terms: -1n + n = 0
-10 + -11n = 12 + 0
-10 + -11n = 12

Add '10' to each side of the equation.
-10 + 10 + -11n = 12 + 10

Combine like terms: -10 + 10 = 0
0 + -11n = 12 + 10
-11n = 12 + 10

Combine like terms: 12 + 10 = 22
-11n = 22

Divide each side by '-11'.
n = -2

Simplifying
n = -2

See similar equations:

| 2.5X^2-0.8X=X^2+0.7 | | -3-7=-9+x | | 30X^2+45X-1=-1 | | 3-7=-9+x | | 4X^2-9X+10=10-25X | | 8X^2+4X=X^2-10X | | 160+50b=1000 | | (x+13)(x+7)=-3 | | x^2-y^2+2x+2p= | | 55=-5(a+6) | | (4x+1)5=5 | | 4z-6=3z | | 3x^2-62-72= | | 3(n-1)=5n+3-3n | | P=75-2qs | | 9-n-4= | | 2*+3=10 | | 2x-x+1x-3x= | | -16t^2+40t+555=0 | | 4x-28y=84 | | 8x+6y=250 | | 3w-6w=12 | | 0.8x=-2.0x-3 | | 12h^2-13hj-4j= | | 121x^2-220x-96=0 | | C(n)=15n+90 | | -40z^5+30z^4+25z^3= | | 8x-(5x+4)=4x-33 | | t-7-29=419 | | 8+3(4y+5)= | | 20x+15y=250 | | 9x+5=3x+1 |

Equations solver categories